Determination of critical local straining conditions for solidification cracking at laser beam welding by experimental and numerical methods - Bakir, Nasim; Gumenyuk, Andrey; Rethmeier, Michael (Proceedings in applied mathematics and mechanics, 2024)
The phenomenon of solidification cracking has been the subject of numerous research projects over the years. Great efforts have been made to understand the fundamentals of hot cracking. It is generally agreed that solidification cracks form in the solidification range between the liquidus and solidus temperatures under the combination of thermal, metallurgical and mechanical factors. There is still a need to determine the time‐resolved strain distribution in the crack‐sensitive region in order to analyse the local critical conditions for solidification cracking phenomena. This was a strong motivation for the development of a measurement system used in this study to estimate the local strains and strain rates in the zone where the solidification crack is expected to occur. The laser beam welding experiments were conducted using the Controlled‐Tensile‐Weldability test (CTW test) to apply an external strain condition during welding to generate solidification cracks. The CTW test is a test method for investigating the susceptibility of laser‐welded joints to solidification cracking, in which the sample can be subjected to a defined strain at a defined strain rate during welding. In combination with experimental investigations, numerical simulations provide spatially detailed and time‐dependent information about the strain development during the welding process, especially regarding the critical conditions for solidification cracking. Therefore, this tool was also used in the present study to evaluate the accuracy of measurement methods and to estimate experimentally derived values and their concrete influence on the formation of solidification cracks. By integrating experimental methods and numerical simulations, this study investigates the spatially resolved and temporally changing development of strain during welding, with a particular focus on the critical conditions that lead to the formation of solidification cracks. The use of numerical simulations serves a dual purpose by validating the accuracy of measurement methods and examining experimentally determined values for their actual influence on the formation of solidification cracks. A three‐dimensional finite element (FE) model implemented with ANSYS is used to simulate strains and stresses during welding. The credibility of the model was first established by validation using experimental temperature measurements. Subsequently, structural simulations were carried out under external load. The results of the simulations showed commendable agreement with the strain measurements performed using the developed technique.